Dissecting Anvil Cloud Response to Sea Surface Warming. Issue 15 (6th August 2021) - Beydoun, Hassan; Caldwell, Peter M.; Hannah, Walter M.; Donahue, Aaron S.
Abstract: We derive an anvil cloud diagnostic from the continuity equation of cloud ice and apply it to the output of convection‐permitting Energy Exascale Earth System Model (E3SM) simulations run in radiative‐convective equilibrium mode. This diagnostic shows that anvil cloud fraction can be reliably diagnosed as a product of cloud detrainment and lifetime. Detrainment is found to be approximated well by a product of clear sky convergence and cloud ice mixing ratio, while cloud lifetime is dominated by sedimentation. Taken together, this diagnostic expresses anvil cloud fraction as a function of five physically measurable quantities. Of these, clear‐sky convergence changes drive the anvil cloud reduction with warming while an increase in cloud ice mixing ratio buffers the decrease. Accordingly, this study provides a theoretical foundation upon which the Stability‐Iris hypothesis can be tested. Plain Language Summary: Horizontally extensive "anvil clouds" are formed in the upper troposphere by horizontal outflow from deep convection. As the planet warms, the environment around anvil clouds becomes more buoyantly stable, reducing horizontal outflow. The Stability‐Iris hypothesis (Bony et al.,  2016, https://doi.org/10.1073/pnas.1601472113 ) suggests that this reduced outflow will cause anvil cloud extent to decrease under warmer conditions. In this paper, we derive an equation linking horizontal outflow to anvil clouds and find that the Stability‐Iris mechanism is indeed responsible for the warming induced anvil cloud reduction in our numerical simulations. Key Points: Anvil cloud fraction can be reliably diagnosed as a product of detrainment and cloud lifetime Detrainment can be diagnosed as a product of clear sky convergence and cloud ice mixing ratio The trend of declining clear sky convergence is the strongest contributor to the trend of declining anvil cloud fraction with warming